Patient diaries: Survey of paediatric intensive care units in the United Kingdom and Ireland. Issue 1 (4th October 2019) - Lynch, Fiona; Endacott, Ruth; Latour, Jos M.
Abstract: Aim: The aim of the study was to explore the incidence, use, and scope of patient diaries in paediatric intensive care units (PICUs) in the United Kingdom and Ireland. Design: This was an electronic survey sent to 30 PICUs in the United Kingdom and Ireland. Results: All PICUs (n = 30) responded, and 43% (n = 13) offered diaries. For those units that did not supply diaries, the reasons given were concerns around the legal and professional implication of using diaries. Parental/carer consent to use a diary was obtained informally (79%, n = 11), and once there was agreement to provide a diary to parents, diaries were usually started immediately (72%, n = 12). Parents were the main contributors to the diaries (94%, n = 17), and the diaries were populated with photographs (94%, n = 15), drawings (100%, n = 16), and stickers (94%, n = 15). The reasons for offering diaries were to fill gaps in memories, to engage with families, and to explain what has happened in lay language. The owner of the diary was reported to be the family (82%, n = 14) and the child (12%, n = 2). Conclusions: The use of patient diaries is an evolving intervention in paediatric intensive care settings in the United Kingdom and Ireland. This national survey has provided a clearer picture of how this intervention is used in the United Kingdom and Ireland. PICU patient diaries are used in a significant number of units, and how these are used is relatively standardized, although in some different ways from general ICUs. Relevance to clinical practice: This survey provides a baseline for future exploration, understanding, and promotion of patient diaries, as a well evaluated tool for the critically ill child and his or her family.